Antifungal activity of natamycin and development of an edible film based on hydroxyethylcellulose to avoid Penicillium spp. growth on low-moisture mozzarella cheese. (15th January 2022) - Torrijos, Raquel; Nazareth, Tiago Melo; Calpe, Jorge; Quiles, Juan Manuel; Mañes, Jordi; Meca, Giuseppe
Abstract: This study aimed to investigate natamycin's in vitro antifungal activity against Penicillium strains and determine its antifungal effect on Mozzarella cheese slices contaminated with P. commune . Besides, the residual content of natamycin in the samples was assessed during the storage. Natamycin was either sprayed on the cheese surface or incorporated into an edible hydroxyethylcellulose film at concentrations of 0, 0.25, 0.5, and 1 mg/dm 2 . Natamycin showed an antifungal effect against all Penicillium strains with MIC values ranging from 1.6 to 3.1 μg/mL and MFC values ranging from 12.5 to 200.0 μg/mL. Moreover, both applied techniques significantly ( p ≤ 0.05) reduced the population of P. commune and increased the shelf life of Mozzarella cheese slices in a dose-dependent manner. The higher dose tested (1 mg/dm 2 ) reduced the fungal population in 5.28 Log CFU/g and 4.15 Log CFU/g for spray and film treatment compared to control, respectively. Furthermore, the samples treated with hydroxyethylcellulose antifungal film showed a lower residual concentration of natamycin on the surface than spray treatment. These findings indicate that natamycin-containing hydroxyethylcellulose films may be used on Mozzarella cheese rather than direct applications, as a biodegradable antifungal system, without sacrificing food safety. Highlights: Natamycin demonstrated in vitro antifungal effect against all Penicillium strains. The spray of natamycin reduced the fungal growth regardless of the doses assayed. Hydroxyethylcellulose films with natamycin reduced fungal growth on Mozzarella. Hydroxyethylcellulose films gradually released natamycin on the cheese surface. Hydroxyethylcellulose films with natamycin improve Mozzarella cheese safety.